Popis familiární formy Creutzfeldt-Jakobovy nemoci - Janoutová, J; Siváková, L; Máslová, L; Hozák, A; Vařechová, K; Janout, V (Epidemiologie, mikrobiologie, imunologie, 2016)
AIM: The analysis of the available reported data and epidemiological investigation data on the cases of Creutzfeld-Jakob disease (CJD) that emerged in the Nový Jičín district in 2001-2011, with a focus on the familial form of the disease. MATERIAL AND METHODS: Data from the Regional Public Health Service of the Moravian-Silesian Region, local Public Health Centre Nový Jičín, were used for the analysis. RESULTS: This is a retrospective report of 10 cases of familial Creutzfeld-Jakob disease (CJD) in the Nový Jičín district in 2001-2011, based on the data from the public health service. Overall eight cases were notified and seven suspected cases were identified retrospectively. Out of these 15 cases, five were concluded to be sporadic CJD and 10 to be familial CJD. The PRNP D178N mutation was found in two fatal cases from 2002 and 2003. Genetic investigation of their relatives was not performed for ethical reasons. CONCLUSION: The high incidence of familial CJD in the Nový Jičín district in 2001-2011 is surprising, but the retrospective investigation failed to provide further evidence to understand this outbreak.
Keywords: Česká republika; Czech Republic; Retrospective Studies; retrospektivní studie; lidé; Creutzfeldtova-Jakobova nemoc; Creutzfeldt-Jakob disease - familial form - cases in the Nový Jičín district - D178N mutation.; Creutzfeldt-Jakob Syndrome; Humans